Exploring the Impact of Differentiated Per-Lane Speed Limits on Traffic Safety of Freeways with Considering the Compliance Rate - Meiyu Liu; Jing Shi (Journal of Advanced Transportation)
This is a subsequent study of a two-lane cellular automata (CA) traffic simulation model proposed by the authors. The current study focused on understanding the impacts of the configuration of the differentiated per-lane speed limit (DPLSL) and its compliance rate on traffic safety indexes, including lane-changing frequency, the coefficient of variation of speed, and incident rate of dangerous situations. The results indicate that freeway sections with DPLSL, especially the ones with complex DPLSL, have potentials to reduce the speed variation, lane changing frequencies, and chances of dangerous situations, resulting in higher traffic safety levels. Furthermore, under DPLSL configurations, the compliance rate of the lane of slow vehicles could positively affect the traffic safety levels. Specifically, as the decrease of the compliance rate, lane changing frequency slightly increases, the coefficient variation of speed especially of the outer lane increases, and the incident rate of the overtaking-on-the-right circumstances increases. In contrast to the simple DPLSL, freeway segments with the complex DPLSL configuration are more sensitive to the influence of the compliance rate.